African Governments’ Responses to the Covid-19 Pandemic and its Impact on Women: A Case Study of Nigeria - Ilesanmi, Omotola Adeyoju; Agu, Chinyere Rita (Journal of Contemporary International Relations and Diplomacy, 2024)
The emergence of the COVID-19 pandemic in Africa created widespread socio-economic and healthcare challenges for countries, and peoples’ lives and livelihoods. Like other public health emergencies, the COVID-19 pandemic is gendered, and affected men, women, boys and girls in complex and varying ways; exacerbating the existing deep-seated gender inequalities in African societies. Similarly, the response measures adopted by African governments, including Nigeria, in addressing the disease outbreak and preventing its spread had a disproportionate impact on women and girls. To cushion the impact of the measures adopted against the disease, the Nigerian government created socio-economic initiatives and programs for the citizenry. However, these measures did not adequately integrate a gender perspective in their design and implementation. Using a desk review of secondary sources, the paper examines the impact of the COVID-19 pandemic and the response measures adopted by the Nigerian government. It concludes that the failure by policy makers in Nigeria, and Africa generally, to effectively mainstream gender into the design and implementation of these policies, and underrepresentation of women in government taskforces limited the effectiveness of the measures.